A coumarin embedded highly sensitive nitric oxide fluorescent sensor: kinetic assay and bio-imaging applications. Issue 41 (15th October 2020) - Maiti, Debjani; Islam, Abu Saleh Musha; Sasmal, Mihir; Dutta, Ananya; Katarkar, Atul; Ali, Mahammad
Abstract : A benzo-coumarin based molecular probe efficiently and selectively senses nitric oxide (NO) through the formation of 1, 2, 3, 4-oxatriazole in purely aqueous medium which helps to monitor the exogenous and endogenous NO. Abstract : Fluorescence spectroscopy is a significant bio-analytical technique for specific detection of nitric oxide (NO) and for broadcasting the in vitro and in vivo biological activities of this gasotransmitter. Herein, a benzo-coumarin embedded smart molecular probe (BCM) is employed for NO sensing through detailed fluorescence studies in purely aqueous medium. All the spectroscopic analysis and literature reports clearly validate the mechanistic insight of this sensing strategy i.e., the initial formation of 1, 2, 3, 4-oxatriazole on treatment of the probe with NO which finally converted to its carboxylic acid derivative. This oxatriazole formation results in a drastic enhancement in fluoroscence intensity due to the photoinduced electron transfer (PET) effect. The kinetic investigation unveils the second and first-order dependency on [NO] and [BCM] respectively. The very low detection limit (16 nM), high fluorescence enhancement (123 fold) in aqueous medium and good formation constant ( K f = (4.33 ± 0.48) × 10 4 M −1 ) along with pH invariability, non-cytotoxicity, biocompatibility and cell permeability make this probe a very effective one for tracking NO intracellularly.